The price of innovation - the role of drug pricing in financing pharmaceutical innovation. A conceptual framework - Santiago G. Moreno; David Epstein (Taylor & Francis Group, 2019)
The debate on drug prices has reached new heights with the controversy around the role of prices in promoting innovation. Critics claim that prices of innovative drugs are excessive and argue that lowering prices will not harm the flourishing innovation. On the opposite end, the pharmaceutical industry insists that restrictive pricing policies will have a detrimental impact on their ability to generate innovation. Amid these two divergent positions, this manuscript presents a conceptual framework to better understand the role played by drug prices to influence the ability of pharmaceutical firms to raise money in capital markets and hence finance pharmaceutical innovation. We argue that deviations from established value-based pricing principles, by either firms or payers, will distort access by firms to capital and lead to an undesirable level of innovation in the long term. We hope that this framework helps policy-makers anticipate the impact of their proposals, and ultimately guide policies towards setting optimal drug prices as a means to maximise social welfare.